Nutritionist’s Role in Dietary Management of Patients with Cancer - Amal Agila,; Ambarka Kreim, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study is to know the effect of appropriate nutrition on developing the health of children with cancer during their treatment. Also, it is to investigate personal dietary counseling by a nutritionist to maintain body weight. and to prevent malnutrition compared to standard medical care. A cross-sectional study was conducted on 100 children with cancer aged from 1 to 15 years in Tripoli, Libya from 1 March to 30 August, 2023. The cross-sectional study also involved 100 parents of children with cancer aged from 23 to 68 years old. Results showed that about 51% of cases had leukemia and 70 % of cancers were hereditary. Most cases in stage II (47%) and 44% of cases underwent chemotherapy dose treatment. Before treatment, 20% of children with cancer had normal BMI and 40% were underweight. But, 49% of children with cancer gained weight after treatment and they ate hospital diet. There was a slight increase in the values of BMI before and after treatments. The values of the BMI measurements before and after cancer treatment were a statistically significant different (P=0.047). Endpoints were weight loss before treatment, Low BMI and malnutrition. Consequently, early and intensive individualized dietary counseling by a nutritionist help promoting healthy weight. تهدف هذه الدراسة إلى معرفة تأثير التغذية المناسبة على تطوير صحة الأطفال المصابين بالسرطان أثناء علاجهم. كما تهدف إلى التحقيق في الاستشارة الغذائية الشخصية من قبل أخصائي التغذية للحفاظ على وزن الجسم. ومنع سوء التغذية مقارنة بالرعاية الطبية القياسية. أجريت دراسة مقطعية على 100 طفل مصاب بالسرطان تتراوح أعمارهم بين 1 إلى 15 عامًا في طرابلس، ليبيا من 1 مارس إلى 30 أغسطس 2023. كما شملت الدراسة المقطعية 100 والد لأطفال مصابين بالسرطان تتراوح أعمارهم بين 23 و 68 عامًا. أظهرت النتائج أن حوالي 51٪ من الحالات مصابة بسرطان الدم وأن 70٪ من السرطانات وراثية. خضعت معظم الحالات في المرحلة الثانية (47٪) و 44٪ من الحالات لعلاج جرعات العلاج الكيميائي. قبل العلاج، كان لدى 20٪ من الأطفال المصابين بالسرطان مؤشر كتلة الجسم طبيعي وكان 40٪ يعانون من نقص الوزن. لكن 49% من الأطفال المصابين بالسرطان اكتسبوا وزنًا بعد العلاج وأكلوا نظامًا غذائيًا في المستشفى. كانت هناك زيادة طفيفة في قيم مؤشر كتلة الجسم قبل وبعد العلاج. كانت قيم قياسات مؤشر كتلة الجسم قبل وبعد علاج السرطان مختلفة إحصائيًا بشكل كبير (P = 0.047). كانت النقاط النهائية هي فقدان الوزن قبل العلاج وانخفاض مؤشر كتلة الجسم وسوء التغذية. وبالتالي، فإن الاستشارة الغذائية الفردية المبكرة والمكثفة من قبل أخصائي التغذية تساعد في تعزيز الوزن الصحي